Obstetric and perinatal outcomes of pregnancy in patients with repeated implantation failure - Tzu Hsuan Chin; Ya Chiung Hsu; Yung Kuei Soong; Chyi Long Lee; Hsin Shih Wang; Hong Yuan Huang; Hsien Ming Wu; Hsing Tse Yu; Shang Yu Huang; Chia Lin Chang (Elsevier, 2019)
Objective: Despite the great advance of assisted reproductive technology (ART) in recent decades, many IVF patients failed to achieve a pregnancy even after multiple IVF-ET attempts. These patients are considered to have repeated implantation failure (RIF). While exhausting efforts have been devoted to the improvement of pregnancy rate in RIF patients, it is not clear whether RIF patients have aberrant obstetric or perinatal outcomes after they eventually achieved a pregnancy. Materials and methods: Taking advantage of a relatively large database of IVF-ET cycles at the Chang Gung Memorial Hospital, we compared obstetric and perinatal outcomes of RIF patients who have a successful pregnancy after IVF-ET treatment(s) to those of control IVF-ET patients. Results: Because multiple pregnancies are associated with a high risk of obstetric complications, we restricted the analysis to patients who had singleton pregnancies. Analysis of a total of 596 control and 46 RIF cases showed the rates of almost all obstetric and perinatal outcomes investigated are not different between the two groups. However, the rate of placental abruption in the RIF group (4.35%) appeared to be significantly higher than that of controls (0.50%; OR = 8.99). This difference is still statistically significant after adjustment with the age (adjusted OR = 8.2). Conclusion: While the rates of a spectrum of obstetric and perinatal outcomes are normal in RIF patients, these patients could have an enhanced risk of placental abruption. However, investigations with a large sample size are needed to substantiate this inference. Keywords: RIF, Repeated implantation failure, Placental abruption, IVF, Embryo transfer